2021
DOI: 10.1038/s41598-021-95708-x
|View full text |Cite
|
Sign up to set email alerts
|

Angular and linear measurements of adult flexible flatfoot via weight-bearing CT scans and 3D bone reconstruction tools

Abstract: Acquired adult flatfoot is a frequent deformity which implies multiple, complex and combined 3D modifications of the foot skeletal structure. The difficult thorough evaluation of the degree of severity pre-op and the corresponding assessment post-op can now be overcome by cone-beam (CBCT) technology, which can provide access to the 3D skeletal structure in weight-bearing. This study aims to report flatfoot deformities originally in 3D and in weight-bearing, with measurements taken using two different bone segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…Furthermore, the reliability of the software algorithm we describe has been previously reported in 2 studies, and we found that it was excellent in our analysis as well. 18,28 A number of authors have used similar techniques and the same software with reproducible results, and we included a control group (normal feet) where there was no difference from conventional manual methods, suggesting the technique is reproducible. This study cannot ascertain the cause for the differences seen, nor prove that rotation is responsible and further work with larger sample sizes is required looking at coronal plane deformities and how they relate to sagittal and axial deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reliability of the software algorithm we describe has been previously reported in 2 studies, and we found that it was excellent in our analysis as well. 18,28 A number of authors have used similar techniques and the same software with reproducible results, and we included a control group (normal feet) where there was no difference from conventional manual methods, suggesting the technique is reproducible. This study cannot ascertain the cause for the differences seen, nor prove that rotation is responsible and further work with larger sample sizes is required looking at coronal plane deformities and how they relate to sagittal and axial deformities.…”
Section: Discussionmentioning
confidence: 99%
“…The automated software has been validated against measurements on conventional radiographs in previous foot and ankle studies and further verified in this study by post hoc surgeon review for all the parameters analyzed. 10,13 Finally, we recognize that the WBCT is a static radiologic representation of osseous structures and direct application to clinical management may be limited. Further studies are needed to compare pre- and postoperative WBCT to determine the true effect of TN soft tissue release with or without bony procedures.…”
Section: Discussionmentioning
confidence: 99%
“…FDA-approved clinical software for 3D anatomic modeling (Disior Bonelogic, version 2.0) allowed for precise, automated multisegment volume and surface area rendering, previously validated in the foot and ankle literature. 10,13 The axial plane anterior-posterior axis was determined from principal components analysis of the distal tibial plafond. Similar calculation for the anatomic axes of the calcaneus, talar body, talar head, navicular, medial cuneiform, and first metatarsal were compared to the reference anterior-posterior axis.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed two sets of feet: the first dataset consists of three fresh-frozen full lower limbs (male; age: 77.7 ± 7.8 years; height: 175.3 ± 5.8 cm; weight: 87.0 ± 15.7 Kg) from cadaver dissection with no history of previous pathologies and was meant to overcome limits due to ionizing radiation during CT scans (normal feet dataset). The second dataset includes three patients (female/male: 1/2; age: 47.3 ± 20.1 years; height: 175.7 ± 9.0 cm; weight: 74.7 ± 7.0 Kg) affected by flat feet taken from a previous study [ 29 ], to provide an initial exploitation on pathological feet of the presently proposed ARS (flat feet dataset).…”
Section: Methodsmentioning
confidence: 99%